The columnar to equiaxed transition of horizontal unsteady-state directionally solidified Al-Si alloys - CARVALHO, Diego de Leon Brito (2015)
Experiments were conducted to investigate the influence of thermal parameters on the columnar to equiaxed transition during the horizontal unsteady-state directional solidification of Al-Si alloys. The parameters analyzed include the heat transfer coefficients, growth rates, cooling rates, temperature gradients and composition. A combined theoretical and experimental approach is developed to determine the solidification thermal variables considered. The increasing solute content in Al-Si alloys was not found to affect significantly the experimental position of the CET which occurred for cooling rates in the range between 0.35 and 0.64 K/s for any of three alloy compositions examined. A comparative analysis between the results of this work and those from the literature proposed to analyze the CET during upward vertical solidification of Al-Si alloys is reported and the results have shown that the end of the columnar region during horizontal directional solidification is abbreviated as a result of about six times higher thermal gradient than that verified during upward unidirectional solidification of alloys investigated.